2002
DOI: 10.1039/b109019b
|View full text |Cite
|
Sign up to set email alerts
|

A tetranuclear nickel(ii) complex assembled from an asymmetric compartmental ligand and bearing an intramolecular [H3O2]– bridge

Abstract: The asymmetric di-aminic compartmental ligand HL5 forms a tetranuclear nickel(II) complex in which the core is assembled from two confacial bioctahedra [Ni...Ni, approximately 2.90 A]; the open faces of the bioctahedra are joined at the O atoms of two mu-cresolato bridges [Ni...Ni, 3.72 A], and the shared faces of the bioctahedra are linked by a tetradentate (mu 4, eta 2)-perchlorate anion and by an unusual tetradentate (mu 4, eta 2)-[H3O2]-bridge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…The phenol-based ligand Hpy2ald, containing the tridentate arm in the 2-position and the carbonyl group in the 6-position of the aromatic ring ate in the synthesis of asymmetric dinucleating ligands. [15] In contrast to the coordination compounds reported by Adams et al, [2,14] the present complexes do not possess dinuclear cores comprised of two metal ions and two ligands. In all complexes, the carbonyl group of the ligand does not coordinate to the metal ions, which partly originates from the presence of a stronger nitrate, bromide or chloride donor anion.…”
Section: Introductioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The phenol-based ligand Hpy2ald, containing the tridentate arm in the 2-position and the carbonyl group in the 6-position of the aromatic ring ate in the synthesis of asymmetric dinucleating ligands. [15] In contrast to the coordination compounds reported by Adams et al, [2,14] the present complexes do not possess dinuclear cores comprised of two metal ions and two ligands. In all complexes, the carbonyl group of the ligand does not coordinate to the metal ions, which partly originates from the presence of a stronger nitrate, bromide or chloride donor anion.…”
Section: Introductioncontrasting
confidence: 75%
“…( Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004) suggested that the presence of such anions, as well as nickel ions, is crucial. [14] All the dinuclear complexes obtained with these in situ generated ligands were found to have very similar crystal structures, comprising a dimetallic core with two bridging phenolato groups from two ligands. In all cases the metalto-ligand ratio was found to be 2:2.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The average bond lengths for PhOϪNi (1.82 Å ) and NϪNi (1.83 Å ) are similar to the values reported for mononuclear salen Ni II complexes. [6] For ROϪNi bonds, the mean distance is 1.87 Å , which is shorter than the usual NiϪO distance in six-coordinate Ni II complexes [7] and close to those in a planar Ni II coordination geometry. [8] In addition, the µ 3 -HO-Ni distance of 1.90 Å here is also shorter than the reported values in six-coordinate Ni II .…”
Section: Preparation and Characterizationmentioning
confidence: 94%
“…[14][15][16][17] We have previously commented that the precursor for the assembly of a tetranuclear nickel() complex of an asymmetric compartmental ligand in which the nickel() atoms were bridged by an intramolecular (µ 4 ,η 2 :η 2 )-[H 3 O 2 ] Ϫ anion and a tetradentate (µ 4 ,η 2 :η 2 )-perchlorate anion could have been a µ-hydroxo bridged dinickel() complex. 18 It is similarly plausible that the reaction giving 1 should proceed (Scheme 1)…”
mentioning
confidence: 99%